2015
DOI: 10.1016/j.eats.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Transosseous Medial Meniscal Root Repair Using a Modified Mason-Allen Suture Configuration

Abstract: Medial meniscal tears are among the most common injuries to the knee joint. Loss of the meniscus has been linked to increased contact pressures on the adjacent articular cartilage and progression of degenerative changes in the knee. A subset of tears known as "root tears" involves the insertion of the posterior horn of the meniscus to the bone. Arthroscopic partial meniscectomy for root tears led to undesirable outcomes, which prompted surgeons to explore restorative procedures. Multiple repair techniques have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A number of techniques have been introduced to reduce the residual meniscal extrusion after the MMPRT repair. 15 , 16 , 17 , 18 , 19 , 20 , 21 Koga et al. 17 reported a novel technique using centralization suture.…”
Section: Discussionmentioning
confidence: 99%
“…A number of techniques have been introduced to reduce the residual meniscal extrusion after the MMPRT repair. 15 , 16 , 17 , 18 , 19 , 20 , 21 Koga et al. 17 reported a novel technique using centralization suture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have found that poor prognostic factors after PMMR tears repair are modified outerbridge classification grade ≥3, chondral lesions, varus alignment >5°, older age, female sex, high BMI and medial meniscus extrusion [ 8 , 16 ]. To improve the poor prognosis of PMMR tears repair, studies on transtibial pull-out fixation have focused on the meniscus–suture interface using different fixation techniques, such as the modified Mason–Allen technique or two simple sutures [ 17 , 18 ]. However, to date, few studies have examined tibial fixation methods in PMMR repair.…”
Section: Introductionmentioning
confidence: 99%
“…The transosseous suture pullout technique is a commonly performed procedure for various knee surgeries, such as tibial spine fixation, 1 root repair, 2 and meniscal repairs. 3 , 4 , 5 Once these transosseous sutures are pulled out through the bone tunnel, they can be secured over a screw, washer, or an endobutton. 6 However, these fixation techniques of transosseous sutures require an implant, which adds to the cost of surgery.…”
Section: Introduction (With Video Illustration)mentioning
confidence: 99%